EVALUASI LAYANAN PELANGGAN BERBASIS QUALITY FUNCTION DEPLOYMENT (QFD) STUDI KASUS: PT. MITRA NASIONAL KUALITAS, JAKARTA - Hasti Purnasari, Taufik Djatna dan Hartrisari Hardjomidjojo (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Facing the problem of market condition dan competition shifting, lack of sufficient information about customers’ needs dan firm competencies are challenges to business organizations. Customers have requirements that they do not reveal dan causing the firm’s failure of meeting the customers’ satisfaction. Therefore, firms need to manage their relationship toward customer, so as to gain a better customer insight by implementing the Customer Relationship Management approach. This research is aiming at evaluating service quality to meet customer’s satisfaction dan planning an improvement for service quality based on customers’ judgment at Mitra Nasional Kualitas Jakarta, Ltd using Quality Function Deployment concept. The voice of customers is identified using questionnaire dan translated into service requirements by building a House of Quality matrix. In the end, evaluation results show that these service attributes: suitableness of limit order dan special discount for loyal customer got improvement proportion point as 1.7 dan indicate these service attribute have not met the customers’ satisfaction yet. The service recovery can be done by improving the quality of staffs’ service attitude, performance of office staff dan distribution staff dan goodness of information flow as well.                 Keywords: CRM, house of quality, QFD, service quality, voice of customers.